Taking punishment into your own hands: an experiment - Dürsch, Peter; Müller, Julia (Journal of economic psychology, 2015)
In a punishment experiment, we separate the demand for punishment in general from the demand to conduct punishment personally. Subjects experience an unfair split of their earnings from a real effort task and have to decide on the punishment of the person who determines the distribution. First, it is established whether the allocator’s payoff is reduced and, afterwards, subjects take part in a second price auction for the right to (physically) carry out the act of payoff reduction themselves. Subjects bid positive amounts and are happier if they get to punish personally.